The financial management of Small, Medium and Micro Enterprises in the rural communities - Motimele, M. E. (My University, 2010)
Financial Management is one of the critical principles in the business enviromnent. This study was conducted to assess the impact of the use of financial statement by SMMEs on to the success of their businesses. ln Chapter one of the study, the researcher gives the background to the research problem. The objectives of the study are also discussed. The research questions are highlighted and the key concepts that are used in the study and defined. The researcher gave the fonnat of the study and concluded the chapter with summary chapter. Chapter two focused on the review of related literature where different sources who explained about the financial management in SMMEs were consulted. The research objectives were restated and intensely discussed. The researcher outlined the challenges he encountered during the research process. The chapter was concluded with a summary chapter. Chapter three discussed the research design and methodology. The rationale for the study was explained in this chapter. The research design, types of research, target population, sampling and the research instruments were all explained in this chapter. The questionnaire construction and questionnaire items were also outlined. The research process was explained in full and the chapter was concluded with a summary. Chapter four discussed the data analysis, where the differences between qualitative and quantitative data analysis were discussed. Findings from other documents were also discussed. The chapter was concluded with a summary. Chapter five summarized all the chapters by the giving conclusion and recommendations.
Thesis (MBA.) -- University of Limpopo, 2010
Keywords: Financial management; Small, Medium and Micro Enterprises; Rural communities; 658.1592; Small business -- South Africa -- Finance; Business enterprises -- South Africa; Financial statements -- South Africa